CYCLIZATION AND HYDROGENATION OF (+)-CITRONELLAL TO MENTHOLS OVER ZnBr2 AND Ni CATALYSTS SUPPORTED ON γ-Al2O3 - Elvina Dhiaul Iftitah; M. Muchalal; Wega Trisunaryanti; Ria Armunanto (Indonesian Journal of Chemistry, 2010)
Two steps transformation of (+)-citronellal, cyclization and hydrogenation, on ZnBr2/γ-Al2O3 and Ni/γ-Al2O3 catalyst have been realized with the selectivity to cyclization products (isopulegols) was very high (yield up to ~92.58%) over ZnBr2/γ-Al2O3 under mild condition (90 °C and 1 atm nitrogen atmosphere) with high Brønsted acid concentration, while at the same time very low cyclization rates were achieved over Ni/γ-Al2O3 with low or no Brønsted acidity, respectively. The highest cyclization rates were observed over Ni/ZnBr2/γ-Al2O3 under mild condition (90 °C and 1 atm hydrogen atmosphere). The second step transformation towards cyclization products, hydrogenation to menthols, was performed with Ni/γ-Al2O3 under hydrogen atmosphere. Surprisingly the one-step transformation of (+)-citronellal into menthols was investigated over Ni/γ-Al2O3 with yield ~84% under hydrogen atmosphere (90 °C, 1 atm) by exploiting the presence of acidic and hydrogenation sites on the catalyst surface. On the Ni/γ-Al2O3 catalyst it was found that the cyclization of (+)-citronellal to isopulegols occurs on the surface of the support. In the presence of the noble metal, the isopulegols are further hydrogenated to the menthols.